Sagot :
Given : f(x) = 2x + 1
Solution : f(-3)
- [tex] \large {\tt{f(x) = 2x + 1 }}[/tex]
- [tex] \large{ \tt{f( - 3) = 2( - 3) + 1}}[/tex]
- [tex] \large{ \tt{ \purple{f( - 3) = - 5}}}[/tex]
• • • • • • • • • • • • • • • • • • • • • • • • • • • • • •
Solution : f(1)
- [tex] \large{ \tt{f(x) = 2x + 1}}[/tex]
- [tex] \large {\tt{f(1) = 2(1)+ 1}}[/tex]
- [tex] \purple{ \large{ \tt{f(1) = 3 }}}[/tex]
• • • • • • • • • • • • • • • • • • • • • • • • • • • • • •
Solution : f(4)
- [tex] \large{ \tt{f(x) = 2x + 1}}[/tex]
- [tex] \large{ \tt{f(4) = 2(4) + 1}}[/tex]
- [tex] \purple{ \large{ \tt{f(4) =9 }}}[/tex]
• • • • • • • • • • • • • • • • • • • • • • • • • • • • • •
#ILoveMathButILoveYouMore
Hello! Sorry but, I'm too lazy to put some explanation, fr, hope u understand. Have a nice day!